A new method for autonomous control of complex job shops – Integrating order release, sequencing and capacity control to meet due dates. (January 2017) - Grundstein, Sebastian; Freitag, Michael; Scholz-Reiter, Bernd
Highlights: This article presents a new method for autonomous manufacturing control particularly designed for meeting due dates. Order release, sequencing and capacity control are considered. The basic problem comprises complex job shop manufacturing with customer orders. Our method is benchmarked with established control methods using event-discrete simulation. Abstract: Due to the development of Cyber-Physical Production Systems, autonomous control of manufacturing processes is of increasing significance. Particularly, these manufacturing control approaches have considerable potential in job shop manufacturing. However, research in this field tends to focus on subtasks of manufacturing control without considering the interdependencies. This article presents the autonomous production control method (APC), which integrates all control tasks – order release, sequencing and capacity control – to meet due dates. The APC is benchmarked with established method combinations using event-discrete simulation. The results demonstrate the potential of our method to meet due dates and emphasise the method's relevance for practical applications.